2021
DOI: 10.1002/ecs2.3702
|View full text |Cite
|
Sign up to set email alerts
|

Mesopredator frugivory has no effect on seed viability and emergence under experimental conditions

Abstract: Members of the order Carnivora are a unique and important seed disperser who consume and deposit undamaged seeds while providing regular long-distance seed dispersal opportunities. Some members of Carnivora, such as coyotes (Canis latrans), are undergoing range expansions which may help the plant species they consume colonize new locations or replace dispersal services provided by recently extirpated species. In this study, we evaluated aspects of the seed dispersal effectiveness of coyotes and gut passage tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Thus, depending on coyote bowel movement speeds, they have the potential to spread Russian olive seeds a long distance from the source tree. For example, coyotes have been shown to pass other plant seeds up to 24 hours after consumption and deposit them up to 7 km away (Draper et al 2021). Numerous plants have been documented to germinate from coyote scat prior to this experiment (Cypher and Cypher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, depending on coyote bowel movement speeds, they have the potential to spread Russian olive seeds a long distance from the source tree. For example, coyotes have been shown to pass other plant seeds up to 24 hours after consumption and deposit them up to 7 km away (Draper et al 2021). Numerous plants have been documented to germinate from coyote scat prior to this experiment (Cypher and Cypher.…”
Section: Discussionmentioning
confidence: 99%
“…For example, coyotes have been shown to pass other plant seeds up to 24 hours after consumption and deposit them up to 7 km away (Draper et al 2021). Numerous plants have been documented to germinate from coyote scat prior to this experiment (Cypher and Cypher.…”
Section: (A) (B)mentioning
confidence: 99%
“…For example, one study found that an increase in fruit in brown bear (Ursus arctos) diets reduced the average gut-passage time from 14.5 to 6.5 h (Elfström et al, 2013). Conversely, there was no effect of the proportion of fruit in the diet on gut-passage times for coyotes (Draper et al, 2021). Though gut-passage time may be altered when consuming fruit for some species (both decreasing and increasing gut-passage time, Cipollini and Levey, 1997), passage times remain on the order of hours suggesting that regardless of how much fruit was consumed, Carnivorans physiology can accommodate long dispersal distances.…”
Section: Quality Of Seed Dispersal: Local Dispersalmentioning
confidence: 99%
“…Furthermore, the behaviors, life-history traits, and physiology of Carnivora make them distinct from other dispersers. For example, Carnivora often maintain large home ranges (i.e., ursids, Graham and Stenhouse, 2014), gut passage times are long (Escribano-Avila et al, 2014;Draper et al, 2021) which will affect the patterns of seedfall across landscapes and the consequences of those patterns in ways that differ from other frugivores (Schupp and Fuentes, 1995;Jordano et al, 2007;Martínez et al, 2008). Differences in seed disperser gut-passage time and post-consumption movement can influence dispersal distances, while their habitat use and defecation patterns can influence micro-site characteristics and degree of seed clumping that will influence plant recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…This variation in seed dispersal may be most evident in two general types of systems: 1) where fruit is a supplementary food item that is less preferred to a food item that can be defended by dominant individuals, leading to greater quantities of seeds dispersed by subordinate individuals supplementing their diets with fruit and 2) where fruit is the preferred food item that is defended by dominant individuals, leading to greater quantities of seeds dispersed by dominant individuals than subordinates (Figure 1). For example, coyotes (Canis latrans) are social carnivores with highly variable diets that often include fruit (Mastro, 2011;Parker, 1995), and fruit consumption by coyotes can provide seed-dispersal services for a wide range of plant species across North America (Bartel & Orrock, 2021;Cypher & Cypher, 1999;Draper et al, 2021;Roehm & Moran, 2013;Willson, 1993) et al, 1996), it is likely that subordinate individuals consume greater amounts of fruit (a secondary food item), transporting substantially greater quantities of seeds than dominant individuals (Figure 1). Because transient (less-dominant) coyotes also have reduced access to ungulate carcasses than territorial (more-dominant) individuals (Gese, 2001), it is likely that resident status is an important predictor of individual fruit consumption, and subsequent seed dispersal, in coyote populations.…”
Section: Soc I a L Stat Us A F F Ect S T H E Qua N T I T Y Of See D S...mentioning
confidence: 99%